Collaborative Governance Regimes In The One Data Indonesia Forum of South Kalimantan Province - Muhamad Yose Rizal; Budi Kristanto (Dinasti International Journal of Education Management and Social Science, 2025)
This study analyzes the implementation of collaborative governance in the operation of the One Data Indonesia (SDI) Forum of South Kalimantan Province using the Collaborative Governance Regime (CGR) approach. Employing a qualitative case study through interviews, documentation, and policy analysis, the study finds that collaboration within the SDI Forum is supported by an adaptive institutional structure, regulatory backing through Presidential Regulations, Governor Regulations, and Circular Letters, as well as facilitative leadership among stakeholders. The South Kalimantan SDI Forum has demonstrated positive achievements, including national recognition as 4th place in the 2022 provincial SDI evaluation and strengthening data governance through monthly and quarterly reporting. Interviews were conducted with five SDI administrators during July–October 2025. However, collaboration still faces challenges such as data system fragmentation, rotation of structural positions, and dependence on specific individuals. Based on CGR analysis, the Forum has fulfilled the principles of principled engagement, shared motivation, and capacity for joint action, but it is not yet fully institutionalized. The Forum is in a transitional phase from individually driven collaboration toward sustainable, system-based collaboration. This study contributes to refining the CGR model in the context of provincial government data governance in Indonesia.